EFFECTIVE USE OF TECHNIQUES IN VEGETABLE GROWING - Khalilov R.D; Omonov D.S (Western European Studies, 2023)
The article provides information on the possibility of creating favorable conditions for increasing the productivity of onion and garlic onion crops in order to improve the technology of growing vegetables
Keywords: Plug; measurer; seeder; technology